2001
DOI: 10.1073/pnas.121164498
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific overexpression of lipoprotein lipase causes tissue-specific insulin resistance

Abstract: Insulin resistance in skeletal muscle and liver may play a primary role in the development of type 2 diabetes mellitus, and the mechanism by which insulin resistance occurs may be related to alterations in fat metabolism. Transgenic mice with muscle-and liver-specific overexpression of lipoprotein lipase were studied during a 2-h hyperinsulinemic-euglycemic clamp to determine the effect of tissue-specific increase in fat on insulin action and signaling. Muscle-lipoprotein lipase mice had a 3-fold increase in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
515
4
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 660 publications
(550 citation statements)
references
References 39 publications
22
515
4
4
Order By: Relevance
“…n=5 and n=4 for transgenic and control rabbits respectively though we cannot exclude the possibility that transgenic rabbits may have (locally) hepatic insulin resistance associated with the fatty liver [30,31,32], overall effect of LPL overexpression on insulin sensitivity was apparently beneficial. These findings in transgenic rabbits contrast with the results in transgenic mice that showed insulin resistance accompanied by accumulation of TG in their skeletal muscle [16] or liver [4]. Nevertheless, one study reported that there is no effect of the accumulation of TG in skeletal muscle on insulin-stimulated whole-body and muscle-specific glucose uptake [18].…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…n=5 and n=4 for transgenic and control rabbits respectively though we cannot exclude the possibility that transgenic rabbits may have (locally) hepatic insulin resistance associated with the fatty liver [30,31,32], overall effect of LPL overexpression on insulin sensitivity was apparently beneficial. These findings in transgenic rabbits contrast with the results in transgenic mice that showed insulin resistance accompanied by accumulation of TG in their skeletal muscle [16] or liver [4]. Nevertheless, one study reported that there is no effect of the accumulation of TG in skeletal muscle on insulin-stimulated whole-body and muscle-specific glucose uptake [18].…”
Section: Discussionmentioning
confidence: 75%
“…Several previous studies have shown that an imbalance of LPL activity may alter the partitioning of plasma TG between muscle and adipose tissue, and thus influence insulin resistance and obesity. For example, increased LPL in muscle and liver might lead to the over-production of NEFA, to accumulation of TG, and to the subsequent impairment of the insulin signal, resulting in a state of insulin resistance [4]. In addition, LPL activity was found to be higher in visceral adipose tissue of obese mice and humans, which could lead to increased NEFA influx through the portal vein into the liver, and could again result in a state of insulin resistance [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intracellular fat accumulation alters insulin signaling and causes insulin resistance and overactive hepatic gluconeogenesis. 10 Hyperinsulinemia is also a potential mechanism for this fibrosis through direct stimulation of hepatic stellate cell mitogenesis and collagen synthesis. 11 The association between DM and graft cirrhosis was recently analyzed in another study carried out by Burra et al 12 on the use of steatotic grafts in HCVpositive recipients, but they did not confirm a similar correlation.…”
mentioning
confidence: 99%